2012
DOI: 10.4172/2155-6113.s1-008
|View full text |Cite
|
Sign up to set email alerts
|

Image versus Health: The Role of Perceptions of Masculinity on Sexual Risk Behaviors among HIV-Positive African American Men who have Sex with Men and Women

Abstract: Background-HIV prevention has rarely explored the impact of childhood sexual abuse (CSA) across health domains among African American men who have sex with men and women (MSMW). Early sexual experiences may influence perceptions of gender roles, sexual identity, and risks for HIV/AIDS. The attribute of masculinity is commonly associated with strength and success. However, a legacy of racism and oppression may pose challenges for African American men in achieving gender-based milestones. Instead, proxies for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The findings from these qualitative studies are promising, suggesting that men perceive connections between abuse and their current same-sex behavior [32,37,50,52], including high-risk exploration of their sexuality [37], that abusive experiences may result in negative mental health consequences and coping strategies [10,32,50], and that being coerced into same-sex encounters by older men led to "intense internal debate" about their sexual identity and coming to terms with the combined pain and pleasure they derived from these experiences [55]. Nevertheless, these studies are limited; they had small sample sizes (N's = 13 -33), some focused exclusively on Black men, the original study aims were broader than childhood sexual experiences, and/or only a few included in-depth interviews.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The findings from these qualitative studies are promising, suggesting that men perceive connections between abuse and their current same-sex behavior [32,37,50,52], including high-risk exploration of their sexuality [37], that abusive experiences may result in negative mental health consequences and coping strategies [10,32,50], and that being coerced into same-sex encounters by older men led to "intense internal debate" about their sexual identity and coming to terms with the combined pain and pleasure they derived from these experiences [55]. Nevertheless, these studies are limited; they had small sample sizes (N's = 13 -33), some focused exclusively on Black men, the original study aims were broader than childhood sexual experiences, and/or only a few included in-depth interviews.…”
Section: Introductionmentioning
confidence: 83%
“…For these men, CSE with an older male and/or same-sex behavior may be sources of shame and social isolation [44,46,47,[49][50][51]. Further, research suggests that men with histories of sexual abuse are less comfortable with their same-sex attraction than men without such histories [13] and several studies have found that some Black and Latino men who were sexually abused as children experience sexual identity confusion [41,52] or establish a link between their abusive experiences and current same-sex desire [32,50,52]. This study will recognize female perpetrators in the early sexual experiences of MSM and MSMW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these men, CSE with an older male and/or same-sex behavior may be sources of shame and social isolation [ 44 , 46 , 47 , 49 - 51 ]. Furthermore, research suggests that men with histories of sexual abuse are less comfortable with their same-sex attraction than men without such histories [ 13 ], and several studies have found that some black and Latino men who were sexually abused as children experience sexual identity confusion [ 41 , 52 ] or establish a link between their abusive experiences and current same-sex desire [ 32 , 50 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…For these men, CSE with an older male and/or same-sex behavior may be sources of shame and social isolation [44,46,47,[49][50][51]. Furthermore, research suggests that men with histories of sexual abuse are less comfortable with their same-sex attraction than men without such histories [13], and several studies have found that some black and Latino men who were sexually abused as children experience sexual identity confusion [41,52] or establish a link between their abusive experiences and current same-sex desire [32,50,52].…”
Section: Introductionmentioning
confidence: 99%